THE IMPACT OF DYSFUNCTIONAL FAMILY ON ADULT CHILD PORTRAYED IN MY NAME IS LUCY BARTON - Andhika, Annisa Laras (Elite : English and Literature Journal, 2021)
This article entilted “The Impact of Dysfunctional Family on Adult Child Portrayed in My Name is Lucy Barton”explaining about the kinds of dysfunctional family and its behavioral impacts on adult child. My Name is Lucy Barton novel was selected because showing most impactedof dysfunctional condition of familyon adult child and how to survive from it. The aim is to find out kinds of dysfunctional family and behavioral impacts. The study uses kinds of dysfunctional family by Sheryl Benton,psychoanalysis by Murray Bowen, and behavioral impacts by Sharon Martin. Descriptive qualitative method is used by presenting data in words and sentences. Reading and selecting quotations from novel to collect data as library research. The result is the adult child survives from abusive and deficient parents. Alone, hopeless, inadequate, guilty and unlovable as the impacted psychological problems faced by adult child.